In vivo and in silico evaluation of the hepatoprotective potential of aqueous extract of Albizia zygia on carbon tetrachloride-induced liver injury in Wistar albino rats (African Journal of Biomedical Research, 2023)
Albizia zygia DC (Fabaceae) is widely used for the traditonal treatment of malaria, female sterility, yaws, sores, wounds, toothache and bronchial diseases. This present study investigated the in vivo and in silico effects of the aqueous extract of Albizia zygia (AEAZ) leaves on carbon tetrachloride-induced liver damage in wistar albino rats. Carbon tetrachloride (CCl4) was dissolved in parafin (1:1) and administered at a dose of 1ml/kg (i.p.) on the first day. Similarly, groups III, IV and V were treated with carbon tetrachloride at the same dose on the first day followed by oral administration of  quercetin (20mg/kg) and AEAZ (100mg/kg and 200mg/ kg body weight) respectively  for seven days  Molecular docking analysis was conducted using Autodock Vina from PyRX to determine the binding affinities and interactions between compounds present in AEAZ and cytochrome P450 2E1.  Carbon tetrachloride administration caused significant increases in liver enzymes as well as MDA levels and a reduction in SOD, catalase and glutathione. Histology of the liver sections reveal that the normal liver morphology was affected by carbon tetrachloride administration. The result exhibited a significant (p< 0.05) protective effect against CCl4 toxicity by lowering serum levels of ALT, AST, ALP   and increasing glutathione, SOD and catalase. The integrity of the hepatocytes was also preserved. GC-MS analysis revealed the presence of several compounds which when subjected to molecular docking demonstrated varying degrees of binding affinities. Our findings showed that AEAZ was able to protect the animal from carbon tetrachloride-induced liver damage. This study therefore suggests that the extract possesses hepatoprotective activities